Comparison of the gut virus communities between patients with Crohn’s disease and healthy individuals - Ding, Yuzhu; Wan, Mengtian; Li, Zheng; Ma, Xiao; Zhang, Wen; Xu, Min (Frontiers in Microbiology, 2023)
Introduction The escalating incidence of Crohn’s disease (CD), a debilitating ailment that ravages individuals and their families, has become a formidable issue over recent decades. Method In this study, fecal samples from patients with CD and healthy individuals were investigated by means of viral metagenomics. Results The fecal virome was analyzed and some suspected disease-causing viruses were described. A polyomavirus named HuPyV with 5,120 base pairs (bp) was found in the disease group. In a preliminary analysis employing large T region-specific primers, it was found that HuPyV was present in 3.2% (1/31) of healthy samples and 43.2% (16/37) of disease samples. Additionally, two other viruses from the anellovirus and CRESS-DNA virus families were found in fecal samples from CD patients. The complete genome sequences of these two viruses were described respectively, and the phylogenetic trees have been built using the anticipated amino acid sequences of the viral proteins. Discussion Further research is required to elucidate the relationship between these viruses and the onset and development of Crohn’s disease.